Flexible copper-clad laminate
The laminated plate, featuring a polyarylene sulfide resin-based base film, a Ni-containing alloy first metal layer, and a Cu second metal layer, addresses the challenges of stretchability, dielectric properties, adhesion, and dimensional accuracy, making it suitable for high-frequency electronic applications.
Patent Information
- Application Number
- JP2023167537
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Existing laminated plates face challenges in achieving excellent stretchability, low dielectric constant, strong adhesion to metals, and precise dimensional accuracy, particularly when using polyarylene sulfide resin films which often exhibit low adhesion and reactivity with metals and adhesives.
A laminated plate structure comprising a base film made of a resin composition containing a polyarylene sulfide resin (A) and a thermoplastic resin (B) with a glass transition temperature of 140°C or higher or melting point of 230°C or higher, combined with a first metal layer of a Ni-containing alloy and a second metal layer, primarily composed of Cu, to enhance adhesion and dimensional accuracy.
The proposed solution achieves a laminated plate with improved stretchability, low dielectric properties, excellent adhesion to metals, and precise dimensional accuracy, making it suitable for high-frequency applications in electronic devices.
Smart Images

Figure 2025057791000001 
Figure 2025057791000002 
Figure 2025057791000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate plate in which a metal layer is laminated to a base film made of a resin composition containing, as a main component, a polyarylene sulfide-based resin having excellent adhesion to metals and low dielectric properties. [Background technology]
[0002] In recent years, electronic devices such as personal computers and mobile terminals have been using higher frequencies of electrical signals in line with the increase in communication speed and capacity, and printed wiring boards that can handle this are in demand. In particular, the higher the frequency of the electrical signal, the greater the loss (attenuation) of signal power, so printed wiring boards that can reduce the loss of signal power (transmission loss) are required. Transmission loss includes conductor loss on the metal layer side that serves as the conductor and dielectric loss on the board side. To reduce conductor loss, it is preferable to reduce the surface roughness of the copper foil that serves as the conductor, since signals have the property of flowing on the surface of the conductor due to the skin effect in the high frequency range. On the other hand, to reduce dielectric loss, it is preferable to reduce the dielectric properties of the resin base material and adhesive. Flexible boards made of materials that satisfy these properties are required as circuit boards with low transmission loss.
[0003] Patent Document 1 discloses a two-layer flexible substrate in which a base metal layer is formed directly on an insulating film without the use of an adhesive, and a copper conductor layer is formed on the base metal layer. Although the insulating film includes polyimide-based films, polyamide-based films, polyester-based films, polytetrafluoroethylene-based films, polyphenylene sulfide-based films, polyethylene naphthalate-based films, and liquid crystal polymer-based films, the examples only include polyimide, and there is no mention of other insulating films, making the adhesion unclear.
[0004] Furthermore, films using polyarylene sulfide resins, such as polyphenylene sulfide resin (PPS), are used as insulating materials for capacitors and motors, and as heat-resistant tapes, due to their excellent heat resistance, flame retardancy, chemical resistance, and electrical insulation. Polyarylene sulfide resins have superior dielectric properties compared to PI and PET, and can therefore be suitably applied in fields such as FPCs and FFCs. However, polyarylene sulfide films generally have issues such as poor adhesion and cohesion to metals and other resins, and poor reactivity with adhesives.
[0005] As an improvement over this, for example, Patent Document 2 describes a biaxially stretched film made of a polyarylene sulfide resin and a thermoplastic resin different from the polyarylene sulfide resin being laminated on at least one side of a metal plate. However, there is no description of a biaxially stretched film made of a thermoplastic resin different from the polyarylene sulfide resin being directly bonded to a metal in a laminate in which a layer made of a low melting point polyphenylene sulfide resin or a non-oriented polyphenylene sulfide sheet is directly laminated with a metal plate. In addition, it is necessary to multi-layer the low melting point polyphenylene sulfide resin layer and the polyarylene sulfide resin and the thermoplastic resin layer different from the polyarylene sulfide resin by co-extrusion, or to laminate with a non-oriented polyphenylene sulfide sheet, which causes problems such as poor productivity. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2006-13152 A [Patent Document 2] JP 2007-276456 A Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention provides a base film having excellent stretchability, a low dielectric constant in the resulting biaxially stretched film, and excellent adhesion to metals, and a laminate using the same having good dimensional accuracy. [Means for solving the problem]
[0008] As a result of sincere investigations into solving the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by using a laminate comprising a base film containing a polyarylene sulfide resin (A) and a thermoplastic resin (excluding polyarylene sulfide resin) (B) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher, a first metal layer made of an alloy containing Ni formed on the surface of the base film, and a second metal layer formed on the surface of the first metal layer, thereby completing the present invention. That is, the present invention relates to the following [1] to
[13] .
[0009] [1] A base film containing a polyarylene sulfide resin (A) and a thermoplastic resin (excluding polyarylene sulfide resins) (B) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher; a first metal layer made of an alloy containing Ni formed on a surface of the base film; a second metal layer formed on a surface of the first metal layer; A laminate comprising: [2] The laminate according to 1, wherein the base film is a biaxially oriented film. [3] A laminate according to claim 1 or 2, wherein the dielectric constant of the base film is 3.3 or less. [4] The laminate according to any one of 1 to 3, wherein the proportion of the polyarylene sulfide resin (A) is 51 to 97% by mass relative to 100% by mass of the total amount of the base film. [5] The laminate according to any one of 1 to 4, wherein the thermoplastic resin (excluding polyarylene sulfide-based resin) (B) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher contains at least one polymer selected from the group consisting of polyphenylene ether-based resins, polycarbonate resins, polyethersulfone resins, polyphenylsulfone resins, polyetherimide resins, polysulfone resins, and fluorine-containing resins. [6] The laminate according to any one of 1 to 5, wherein the blending ratio of the thermoplastic resin (B) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher (excluding polyarylene sulfide-based resin) is 3 to 49 mass% relative to 100 mass% of the total amount of the base film. [7] The first metal layer made of an alloy containing Ni is an alloy containing Ni and Cr, 7. The laminate according to any one of 1 to 6, wherein the metal species constituting the second metal layer is a metal containing 90 mass % or more of Cu. [8] The laminate according to any one of 1 to 7, wherein the first metal layer made of an alloy containing Ni is an alloy containing Ni and Cr, and the proportion of Cr present in the alloy is 3 to 50 mass %. [9] The laminate according to any one of 1 to 8, further comprising a modified elastomer (C) having a reactive group imparted to the base film.
[10] The laminate according to 9, wherein the modified elastomer (C) is an olefin polymer having at least one functional group selected from the group consisting of an epoxy group and an acid anhydride group.
[11] The laminate according to 9 or 10, wherein the proportion of the modified elastomer (C) is in the range of 1 to 15 mass % relative to 100 mass % of the total amount of the base film.
[12] The laminate according to any one of claims 1 to 11, further comprising 0.01 to 5 mass% of a silane coupling agent (D) containing at least one functional group selected from an epoxy group, an amino group, and an isocyanate group in the base film.
[13] The laminate according to any one of claims 1 to 12, wherein the thermoplastic resin (excluding polyarylene sulfide resin) (B) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher has an average dispersed diameter of 5 µm or less.
[14] An electronic device using the laminate described in any one of 1 to 13. Effect of the Invention
[0010] According to the present invention, by using a base film having excellent stretchability and dielectric properties, which is made of a resin composition containing a polyarylene sulfide resin (A) and a thermoplastic resin (excluding polyarylene sulfide resin) (B) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher, the adhesion between a first metal layer formed on the surface of the base film and a second metal layer formed on the surface of the first metal layer is improved, and a laminated plate having excellent dimensional accuracy can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described in detail.
[0012] [Base film] The base film according to the present invention refers to a film obtained by kneading raw materials including at least a polyarylene sulfide resin (hereinafter sometimes referred to as "PAS resin") (A) and a thermoplastic resin (excluding polyarylene sulfide resin) (hereinafter sometimes referred to as "thermoplastic resin") having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher (B) using an extruder or the like to obtain a resin composition, and then biaxially stretching the resin composition. The kneading method and stretching method will be described in detail later.
[0013] The base film contains at least a polyarylene sulfide resin (A) and a thermoplastic resin (excluding a polyarylene sulfide resin) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher as raw materials. The base film may contain a modified elastomer (C) having reactive groups for the purpose of imparting functionality, stretchability, and other toughness.
[0014] In this case, the base film may have a continuous phase and a dispersed phase, in which the continuous phase contains a polyarylene sulfide resin, and the dispersed phase contains a thermoplastic resin (excluding polyarylene sulfide resin) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher. The modified elastomer (C) is present on the surface of the particles of the thermoplastic resin (B) (i.e., the interface between the matrix and the particles), within the particles of the thermoplastic resin (B), or as particles (dispersed phase) separate from the particles of the thermoplastic resin (B).
[0015] The average dispersion diameter of the dispersed phase made of the thermoplastic resin (B) is 5 μm or less, preferably 0.1 μm or more and 5 μm or less, and more preferably 0.2 μm or more and 3 μm or less. If the average dispersion diameter of the dispersed phase is within the range of 0.1 μm or more and 5 μm or less, it is possible to obtain a base film that maintains the physical properties as an insulating base material and has excellent adhesion to metals.
[0016] The base film of the present invention preferably has a dielectric constant of 3.3 or less and a dielectric dissipation factor of 0.005 or less at a frequency of 5 GHz. More preferably, the dielectric constant is 3.0 or less and the dielectric dissipation factor is 0.004 or less. If the dielectric constant is 3.3 or less and the dielectric dissipation factor is 0.005 or less, the base film can be suitably used for FPC-related products for high frequency applications.
[0017] The thickness of the base film is not particularly limited as long as it is a thickness that allows the production of a copper-clad laminate, but is preferably within the range of 10 to 500 μm, and more preferably within the range of 20 to 300 μm.
[0018] The present inventors also believe that the modified elastomer (C) also functions as a compatibilizer between the PAS resin (A) and the thermoplastic resin (B), thereby finely dispersing the particles in the matrix, thereby improving the mechanical strength of the film. Furthermore, the present inventors also believe that the combined use of the modified elastomer (C) with a silane coupling agent further improves the adhesiveness at the interface between the matrix and the particles via the modified elastomer (C), thereby further improving the mechanical strength of the film.
[0019] The base film is preferably a biaxially stretched film obtained by biaxially stretching a sheet obtained by extrusion molding. When a biaxially stretched film is produced, the PAS resin (A) constituting the matrix crystallizes with its molecular chains stretched, making it possible to obtain a film with high dimensional precision.
[0020] The stretching ratio in the longitudinal direction (MD direction) of the biaxially stretched film is preferably 1.5 to 4 times, and more preferably 2.0 to 3.8 times. The stretching ratio in the width direction (TD) of the biaxially stretched film is preferably 1.5 to 4 times, and more preferably 2.0 to 3.8 times. The ratio of the stretching ratio in the width direction (TD direction) of the biaxially stretched film to the stretching ratio in the longitudinal direction (MD direction) of the biaxially stretched film (width direction (TD direction) / longitudinal direction (MD direction)) is preferably 0.8 to 1.3, and more preferably 0.9 to 1.2 because this makes it easier to balance the physical properties in the longitudinal direction and the physical properties in the width direction.
[0021] [Polyarylene sulfide resin (A)] The polyarylene sulfide resin (A) (PAS resin (A)) is the main component of the base film, and is a component that has the function of imparting excellent heat resistance, chemical resistance, and dielectric properties to the film. The PAS resin (A) is a polymer containing a structure in which an aromatic ring and a sulfur atom are bonded (specifically, a structure represented by the following formula (1)) as a repeating unit.
[0022] [ka] (In the above formula, R 1 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group, or an ethoxy group, and each n independently represents an integer of 1 to 4.
[0023] Here, R in the structure represented by formula (1) 1 It is preferable that R is a hydrogen atom. This structure can further increase the mechanical strength of the PAS resin (A). 1 are hydrogen atoms, includes a structure represented by the following formula (2) (i.e., a structure in which a sulfur atom is bonded to an aromatic ring at a para position) and a structure represented by the following formula (3) (i.e., a structure in which a sulfur atom is bonded to an aromatic ring at a meta position).
[0024] [ka] Among these, the structure represented by formula (1) is preferably a structure represented by formula (2). If the PAS resin (A) has the structure represented by formula (2), the heat resistance and crystallinity can be further improved.
[0025] Furthermore, the PAS resin (A) may contain not only the structure represented by the above formula (1) but also structures represented by the following formulas (4) to (7) as repeating units.
[0026] [ka]
[0027] The structures represented by the formulae (4) to (7) are preferably contained in an amount of 30 mol % or less, more preferably 10 mol % or less, of all repeating units constituting the PAS resin (A), which can further increase the heat resistance and mechanical strength of the PAS resin (A). The bonding pattern of the structures represented by formulas (4) to (7) may be either random or block.
[0028] The PAS resin (A) may contain, as a repeating unit, a trifunctional structure represented by the following formula (8), a naphthyl sulfide structure, or the like, in its molecular structure.
[0029] [ka]
[0030] The structure represented by formula (8), naphthyl sulfide structure, etc. are preferably contained in an amount of 1 mol % or less, and more preferably substantially absent, in all repeating units constituting the PAS resin (A). With such a structure, the content of chlorine atoms in the PAS resin (A) can be reduced. The properties of the PAS resin (A) are not particularly limited as long as they do not impair the effects of the present invention. However, the melt viscosity (V6) at 300°C is preferably 100 to 2000 Pa s, and more preferably 120 to 1600 Pa s in order to achieve a good balance between fluidity and mechanical strength.
[0031] Furthermore, it is particularly preferred that the PAS resin (A) has a peak in the molecular weight range of 15,000 to 40,000 when measured by gel permeation chromatography (GPC), has a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) in the range of 5 to 10, and has a non-Newtonian index in the range of 0.9 to 1.3. By using such a PAS resin (A), the chlorine atom content in the PAS resin (A) itself can be reduced to the range of 500 to 2,000 ppm without reducing the mechanical strength of the film, facilitating application to halogen-free electronic and electrical component applications.
[0032] In this specification, the weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) are values measured by gel permeation chromatography (GPC). The measurement conditions for GPC are as follows: [Measurement conditions for gel permeation chromatography] Equipment: Ultra-high temperature polymer molecular weight distribution measuring device (SSC-7000 manufactured by Senshu Scientific Co., Ltd.) Column: UT-805L (Showa Denko) Column temperature: 210℃ Solvent: 1-chloronaphthalene Measurement method: UV detector (360 nm) calibrated with six types of monodisperse polystyrene. The molecular weight distribution and peak molecular weight are measured using the method.
[0033] The method for producing the PAS resin (A) is not particularly limited, but examples thereof include 1) a method in which a dihalogenoaromatic compound, if necessary a polyhalogenoaromatic compound or other copolymerization component is added in the presence of sulfur and sodium carbonate, and polymerized, 2) a method in which a dihalogenoaromatic compound, if necessary a polyhalogenoaromatic compound or other copolymerization component is added in the presence of a sulfidizing agent or the like in a polar solvent, and polymerized, 3) a method in which p-chlorothiophenol, if necessary another copolymerization component is added, and self-condensed, etc. Among these production methods, the above method 2) is versatile and preferred. During the reaction, an alkali metal salt of a carboxylic acid or a sulfonic acid, or an alkali hydroxide may be added to adjust the degree of polymerization.
[0034] Among the above method 2), the following method 2-1) or 2-2) is particularly preferred. In the method 2-1), a water-containing sulfidizing agent is introduced into a mixture containing a heated organic polar solvent and a dihalogeno aromatic compound at a rate at which water can be removed from the reaction mixture, and the dihalogeno aromatic compound and the sulfidizing agent are added, and optionally a polyhalogeno aromatic compound is added, in the organic polar solvent to react with each other, and the amount of water in the reaction system is controlled within a range of 0.02 to 0.5 mol per mol of the organic polar solvent to produce a PAS resin (A) (see JP-A-07-228699). In the method of 2-2), a dihalogeno aromatic compound and, if necessary, a polyhalogeno aromatic compound or other copolymerization component are added in the presence of a solid alkali metal sulfide and an aprotic polar organic solvent, and an alkali metal hydrosulfide and an organic acid alkali metal salt are reacted with each other by controlling the amount of the organic acid alkali metal salt to within a range of 0.01 to 0.9 mol per mol of the sulfur source and controlling the amount of water in the reaction system to within a range of 0.02 mol or less per mol of the aprotic polar organic solvent, thereby producing a PAS resin (A) (see WO2010 / 058713 pamphlet).
[0035] Specific examples of the dihalogeno aromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-dihalodiphenyl sulfone, 4,4'-dihalodiphenyl sulfoxide, 4,4'-dihalodiphenyl sulfide, and the above compounds each having an alkyl group having 1 to 18 carbon atoms on the aromatic ring. Examples of the polyhalogeno aromatic compounds include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, and 1,4,6-trihalonaphthalene. The halogen atoms contained in the above compounds are preferably chlorine atoms or bromine atoms.
[0036] The reaction mixture containing the PAS resin (A) obtained by the polymerization step can be post-treated by a known method, which is not particularly limited, and may, for example, be any of the following methods (1) to (5):
[0037] In the method (1), after the polymerization reaction is completed, the solvent is first distilled off under reduced pressure or normal pressure, either directly from the reaction mixture or after addition of an acid or a base, and then the solid matter remaining after the solvent distillation is washed once or twice or more times with a solvent such as water, the reaction solvent (or an organic solvent having an equivalent solubility to the low molecular weight polymer), acetone, methyl ethyl ketone, or an alcohol, and then neutralized, washed with water, filtered, and dried. In the method (2), after the polymerization reaction is completed, a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, or aliphatic hydrocarbons (a solvent that is soluble in the polymerization solvent used and is a poor solvent for at least the PAS resin (A)) is added to the reaction mixture as a precipitating agent to precipitate solid products such as the PAS resin (A) and inorganic salts, which are then filtered, washed, and dried. In the method (3), after the polymerization reaction is completed, a reaction solvent (or an organic solvent having an equivalent solubility for the low molecular weight polymer) is added to the reaction mixture and stirred, and then the mixture is filtered to remove the low molecular weight polymer. The mixture is then washed once or twice or more times with a solvent such as water, acetone, methyl ethyl ketone, or alcohols, and then neutralized, washed with water, filtered, and dried. In the method (4), after the polymerization reaction is completed, water is added to the reaction mixture, which is then washed with water, filtered, and if necessary, acid is added during the water washing step for acid treatment, and the mixture is then dried. In the method (5), after the polymerization reaction is completed, the reaction mixture is filtered, washed once or more times with the reaction solvent as required, further washed with water, filtered and dried.
[0038] Examples of acids that can be used in the above method (4) include organic acids such as saturated fatty acids, such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, and monochloroacetic acid; unsaturated fatty acids, such as acrylic acid, crotonic acid, and oleic acid; aromatic carboxylic acids, such as benzoic acid, phthalic acid, and salicylic acid; dicarboxylic acids, such as maleic acid and fumaric acid; and sulfonic acids, such as methanesulfonic acid and paratoluenesulfonic acid; and inorganic acids, such as hydrochloric acid, sulfuric acid, sulfurous acid, nitric acid, nitrous acid, and phosphoric acid. Examples of hydrogen salts include sodium hydrogen sulfide, disodium hydrogen phosphate, sodium hydrogen carbonate, etc. However, in practical use, organic acids are preferred because they are less corrosive to metal members. In the above methods (1) to (5), the PAS resin (A) may be dried in vacuum, in air, or in an atmosphere of an inert gas such as nitrogen.
[0039] In particular, the PAS resin (A) post-treated by the above method (4) has an increased amount of acid groups bonded to its molecular terminals, and thus has the effect of enhancing the dispersibility of the thermoplastic resin (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher, or the modified elastomer (C) when mixed with them. The acid group is preferably a carboxyl group. The content of the PAS resin (A) as the main component in the base film may be 51-97% by mass, but is preferably 60-95% by mass. If the content of the PAS resin (A) is within the above range, the film can be imparted with the inherent heat resistance and chemical resistance of the PAS resin, and stretchability can also be maintained. In the present invention, the term "main component" means that the specific resin is contained in an amount of 50% by mass or more, preferably 60% by mass or more, based on the total mass of the resin components used to form the base film.
[0040] [Thermoplastic resins with a glass transition temperature of 140°C or higher or a melting point of 230°C or higher (excluding polyarylene sulfide resins) (B)] The thermoplastic resin (B) (excluding polyarylene sulfide resins) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher according to the present invention (hereinafter, sometimes referred to as "thermoplastic resin") may be any thermoplastic resin having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher.
[0041] The thermoplastic resin (B) may be any thermoplastic resin (excluding polyarylene sulfide resins) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher, and may be, for example, various polymers such as polyphenylene ether resins, polycarbonate resins, polyethersulfone resins, polyphenylsulfone resins, polyetherimide resins, polysulfone resins, fluorine-containing resins, and blends containing at least one of these polymers. Among these, polyphenylene ethers and fluorine-containing resins are preferred from the viewpoints of low dielectric properties and compatibility with PAS.
[0042] The content of the thermoplastic resin (B) in the resin composition constituting the base film may be 3 to 49% by mass, but is preferably 5 to 40% by mass. If the content of the thermoplastic resin (B) is within the above range, the physical properties of the base film are maintained, and the adhesion with the metal layer is effective.
[0043] Polyphenylene ether resin (hereinafter sometimes referred to as "PPE resin") is a component that has the function of providing the base film with a low dielectric constant and low dielectric loss tangent. The PPE resin is a polymer containing the structure represented by the following formula (9) as a repeating unit.
[0044] [ka]
[0045] In the above formula, R 2each independently represents a hydrogen atom, a halogen atom, a primary alkyl group having 1 to 7 carbon atoms, a secondary alkyl group having 1 to 7 carbon atoms, a phenyl group, a haloalkyl group, an aminoalkyl group, a hydrocarbyloxy group, or a halohydrocarbyloxy group in which at least two carbon atoms separate the halogen atom from the oxygen atom, and each m independently represents an integer of 1 to 4.
[0046] Specific examples of PPE resins include homopolymers such as poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), and poly(2,6-dichloro-1,4-phenylene ether), as well as copolymers of 2,6-dimethylphenol and other phenols (e.g., 2,3,6-trimethylphenol and 2-methyl-6-butylphenol). Among these, the PPE resin is preferably poly(2,6-dimethyl-1,4-phenylene ether) or a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol, and more preferably poly(2,6-dimethyl-1,4-phenylene ether).
[0047] The number average molecular weight of the PPE resin is preferably 1,000 or more, more preferably 1,500 to 50,000, and even more preferably 1,500 to 30,000.
[0048] The fluorine-containing resin preferably has at least one reactive functional group selected from the group consisting of a carbonyl group-containing group, a hydroxy group, an epoxy group, and an isocyanate group. Two or more of these reactive functional groups may be included. Among them, a carbonyl group-containing group is preferred from the viewpoint of excellent reactivity with the PAS resin (A). Examples of the carbonyl group-containing group include a group having a carbonyl group between the carbon atoms of a hydrocarbon group, a carbonate group, a carboxy group, a haloformyl group, an alkoxycarbonyl group, an acid anhydride group, and a polyfluoroalkoxycarbonyl group.
[0049] Methods for introducing reactive functional groups into fluorine-containing resins include: (1) using a monomer having a reactive functional group when producing the main chain of a fluorine-containing resin having a reactive functional group by polymerization reaction; (2) producing a fluorine-containing resin having a functional group by polymerization reaction using a chain transfer agent that generates a radical having a reactive functional group; (3) producing a fluorine-containing resin having a functional group by polymerization reaction using a polymerization initiator that generates a radical having a reactive functional group; (4) modifying a fluorine-containing resin by a technique such as oxidation or thermal decomposition; and (5) blending a compound or resin that is compatible with the fluorine-containing resin and contains the functional group.
[0050] Examples of the reactive functional group-containing monomer include a monomer having a carbonyl group-containing group, an epoxy group-containing monomer, a hydroxy group-containing monomer, and an isocyanate group-containing monomer.
[0051] Examples of monomers having a carboxyl group-containing group include unsaturated dicarboxylic acids (maleic acid, itaconic acid, citraconic acid, crotonic acid, himic acid, 5-norbornene-2,3-dicarboxylic acid, maleic acid), their unsaturated dicarboxylic acid anhydrides, unsaturated monocarboxylic acids (acrylic acid, methacrylic acid), vinyl esters (vinyl acetate, vinyl chloroacetate, vinyl butanoate, vinyl pivalate, vinyl benzoate, vinyl crotonate), and the like.
[0052] Examples of the hydroxy group-containing monomer include hydroxy group-containing vinyl ester, hydroxy group-containing vinyl ether, hydroxy group-containing allyl ether, hydroxy group-containing (meth)acrylate, hydroxyethyl crotonate, and allyl alcohol.
[0053] Examples of the epoxy group-containing monomer include unsaturated glycidyl ethers (allyl glycidyl ether, 2-methylallyl glycidyl ether, vinyl glycidyl ether, etc.) and unsaturated glycidyl esters (glycidyl acrylate, glycidyl methacrylate, etc.).
[0054] Examples of the isocyanate group-containing monomer include 2-(meth)acryloyloxyethyl isocyanate, 2-(2-(meth)acryloyloxyethoxy)ethyl isocyanate, and 1,1-bis((meth)acryloyloxymethyl)ethyl isocyanate.
[0055] The amount of reactive functional groups contained in the fluorine-containing resin is preferably 0.01 to 3 mol %, more preferably 0.03 to 2 mol %, and even more preferably 0.05 to 1 mol % of all units constituting the fluorine-containing resin. If the amount of reactive functional groups is within the above range, the reactivity with the PAS resin is excellent and deterioration of flowability can be suppressed.
[0056] The structure of the fluorine-containing resin is not particularly limited, but is composed of at least one type of fluoroolefin unit. For example, tetrafluoroethylene polymer, copolymer with perfluoro(alkyl vinyl ether), hexafluoropropylene, vinylidene fluoride, vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene, and further copolymer with fluorine-free ethylene monomer such as ethylene, propylene, butene, alkyl vinyl ethers, etc. are listed. Specific examples include polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, etc. Among them, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer are preferred from the viewpoint of easy melt extrusion.
[0057] The melting point of the fluorine-containing resin used in the present invention is not particularly limited, but is preferably at least 230° C., more preferably at least 270° C. If the melting point of the fluorine-containing resin is within the above range, heat resistance can be maintained and good melt extrusion stability can be obtained.
[0058] The glass transition temperature of the fluorine-containing resin used in the present invention is not particularly limited, but is 130° C. or lower, more preferably 120° C. or lower, and more preferably 110° C. or lower. If the fluorine-containing resin has the above glass transition temperature, when a stretched film (one form of insulating substrate) is produced using a mixture with the PAS resin (A), peeling at the interface between the PAS resin (A) as a continuous phase and the fluorine-containing resin as a dispersed phase can be suppressed during stretching. This makes it possible to suppress breakage during stretching, and further to obtain a film having excellent mechanical properties.
[0059] [Modified elastomer (C)] The modified elastomer (C) is a component that has a reactive group capable of reacting with at least one of the PAS resin (A) and the thermoplastic resin (B), and thus has the function of improving the mechanical strength (toughness such as folding strength) of the film. The reactive group of the modified elastomer (C) is preferably at least one selected from the group consisting of an epoxy group and an acid anhydride group, and more preferably an epoxy group, which can rapidly react with the functional groups at the molecular ends of the PAS resin (A) and the thermoplastic resin (B).
[0060] Examples of such modified elastomers (C) include copolymers containing repeating units based on an α-olefin and repeating units based on a vinyl polymerizable compound having the above-mentioned functional group, and copolymers containing repeating units based on an α-olefin, repeating units based on a vinyl polymerizable compound having the above-mentioned functional group, and repeating units based on an acrylic ester.
[0061] Examples of the α-olefin include α-olefins having 2 to 8 carbon atoms, such as ethylene, propylene, and butene-1. Examples of the vinyl polymerizable compound having a functional group include α,β-unsaturated carboxylic acids and esters thereof, such as acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters; α,β-unsaturated dicarboxylic acids and esters thereof, such as maleic acid, fumaric acid, itaconic acid, and other unsaturated dicarboxylic acids having 4 to 10 carbon atoms, mono- or diesters thereof, and acid anhydrides thereof; α,β-unsaturated dicarboxylic acids, esters thereof, and acid anhydrides thereof; and α,β-unsaturated glycidyl esters.
[0062] The α,β-unsaturated glycidyl ester is not particularly limited, but examples thereof include a compound represented by the following formula (10).
[0063] [ka]
[0064] In the above formula, R 3 is an alkenyl group having 1 to 6 carbon atoms. Examples of the alkenyl group having 1 to 6 carbon atoms include a vinyl group, a 1-propenyl group, a 2-propenyl group, a 1-methylethenyl group, a 1-butenyl group, a 2-butenyl group, a 1-methyl-1-propenyl group, a 1-methyl-2-propenyl group, a 2-methyl-1-propenyl group, a 2-methyl-2-propenyl group, a 1-pentenyl group, a 2-pentenyl group, a 3-pentenyl group, a 4-pentenyl group, a 1-methyl-1-pentenyl group, a 1-methyl-3-pentenyl group, a 1,1-dimethyl-1-butenyl group, a 1-hexenyl group, and a 3-hexenyl group.
[0065] R 4 are each independently a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 2,2-dimethylpropyl group, a hexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 4-methylpentyl group, a 2,2-dimethylbutyl group, a 2,3-dimethylbutyl group, a 2,4-dimethylbutyl group, a 3,3-dimethylbutyl group, and a 2-ethylbutyl group.
[0066] Specific examples of the α,β-unsaturated glycidyl ester include glycidyl acrylate and glycidyl methacrylate, with glycidyl methacrylate being preferred. The proportion of repeating units based on α-olefin in the modified elastomer (C) is preferably 50 to 95 mass%, more preferably 50 to 80 mass%. When the proportion of repeating units based on α-olefin is within the above range, the stretching uniformity and folding strength of the film can be improved. The proportion of the repeating units based on the vinyl polymerizable compound having a functional group in the modified elastomer (C) is preferably 1 to 30 mass%, more preferably 2 to 20 mass%. When the proportion of the repeating units based on the vinyl polymerizable compound having a functional group is within the above range, not only the desired improvement effect but also good extrusion stability can be obtained.
[0067] The content of the modified elastomer (C) in the base film is preferably 1 to 15 mass %, more preferably 2 to 10 mass %. When the content of the modified elastomer (C) is within the above range, the effect of improving the toughness, such as the folding endurance, of the film is significantly exhibited.
[0068] [Silane coupling agents] In the present invention, it is preferable to use a silane coupling agent as a component having the function of increasing the compatibility (interaction) between the PAS resin (A) and other components (thermoplastic resin (B), modified elastomer (C)), which dramatically improves the dispersibility of the other components in the PAS resin (A) and enables the formation of a good morphology.
[0069] The silane coupling agent is preferably a compound having a functional group capable of reacting with a carboxyl group. The silane coupling agent reacts with any of the PAS resin (A), the thermoplastic resin other than the polyarylene sulfide resin (B), and the modified elastomer (C) to bond strongly to them. As a result, the effect of the silane coupling agent is more pronounced, and the dispersibility of the thermoplastic resin other than the polyarylene sulfide resin (B) and the modified elastomer (C) in the PAS resin (A) can be particularly improved.
[0070] Examples of such silane coupling agents include compounds having an epoxy group, an isocyanate group, an amino group, or a hydroxyl group. Specific examples of the silane coupling agent include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; isocyanato group-containing alkoxysilane compounds such as γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane; amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; and hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane.
[0071] The content of the silane coupling agent in the base film is preferably 0.01 to 5 mass %, more preferably 0.05 to 2.5 mass %. When the content of the silane coupling agent is within the above range, the effect of improving the dispersibility of other components in the PAS resin (A) is significantly exhibited.
[0072] [Styrene-based resin] The base film may contain a styrene resin. The styrene resin is in principle contained in the dispersed phase of the base film. Since the styrene resin has a high compatibility with the polyphenylene ether resin, it may be contained in a form compatible with the polyphenylene ether resin or in a form close to this. The styrene resin has a function of improving the flowability when melted. In this specification, the term "styrene resin" means a resin having a styrene monomer as a main monomer unit.
[0073] The styrene-based resin is not particularly limited, but may be a polymer of a styrene-based monomer. In this case, the styrene-based monomer is not particularly limited, but may be styrene and its derivatives. The styrene derivatives include alkyl styrenes such as methylstyrene, dimethylstyrene, trimethylstyrene, ethylstyrene, diethylstyrene, triethylstyrene, propylstyrene, butylstyrene, hexylstyrene, heptylstyrene, and octylstyrene; halogenated styrenes such as fluorostyrene, chlorostyrene, bromostyrene, dibromostyrene, and iodostyrene; nitrostyrene; acetylstyrene; and methoxystyrene. These styrene-based monomers may be used alone or in combination of two or more.
[0074] The styrene resin may be a homopolymer of a styrene monomer, or a copolymer obtained by copolymerizing two or more kinds of monomers. For example, a copolymer of an unsaturated monomer having a glycidyl group and / or an oxazoline group and a monomer mainly composed of styrene, a block copolymer obtained by copolymerizing a styrene monomer and a conjugated diene compound, and a hydrogenated block copolymer obtained by further hydrogenating the block copolymer may be mentioned. In addition, rubber modified styrene (high impact styrene) may be used by using a rubber component such as polybutadiene, styrene-butadiene copolymer, polyisoprene, or butadiene-isoprene copolymer.
[0075] The above-mentioned styrene-based resins may be used alone or in combination of two or more kinds.
[0076] [Additives] The base film may contain a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, an ultraviolet stabilizer, a lubricant, an antistatic agent, a colorant, a conductive agent, etc., as long as the effects of the present invention are not impaired.
[0077] <Method of producing resin composition> The method for producing the base film is not particularly limited, but includes at least a method in which the PAS resin (A) and the thermoplastic resin (B) are mixed uniformly in a tumbler or Henschel mixer, and then fed into a twin-screw extruder for melt-kneading, and this melt-kneading may be either kneading in a shear flow field or kneading in an extensional flow field, or both. This melt-kneading is preferably performed under conditions in which the ratio of the discharge rate (kg / hr) of the kneaded product to the screw rotation speed (rpm) (discharge rate / screw rotation speed) is 0.02 to 0.2 (kg / hr rpm).
[0078] The set temperature during mixing is selected within the range of +5 to +70° C. above the melting point of the resin having the higher melting point among the PAS resin (A), the thermoplastic resin (B), and the modified elastomer (C), and is more preferably within the range of +10 to +50° C. If the set temperature is lower than the melting points of these resins, the viscosity of the composition increases significantly due to the presence of partially unmelted resin, which increases the load on the twin-screw extruder, which is undesirable from the viewpoint of productivity.
[0079] More specifically, it is preferable to feed each component into a twin-screw extruder and melt-knead it under temperature conditions of about 310°C resin temperature in the strand die at the above-mentioned set temperature. In this case, the discharge rate of the kneaded product is in the range of 5 to 50 kg / hr at a rotation speed of 250 rpm. In particular, from the viewpoint of enhancing the dispersibility of each component, it is preferable that the discharge rate of the kneaded product is 20 to 35 kg / hr at a rotation speed of 250 rpm. Therefore, it is more preferable that the ratio of the discharge rate (kg / hr) of the kneaded product to the screw rotation speed (rpm) (discharge rate / screw rotation speed) is 0.08 to 0.14 (kg / hr rpm).
[0080] <Base film manufacturing method> The method for producing the base film is not particularly limited, but it is preferable that the base film is a biaxially stretched film obtained by biaxially stretching a sheet obtained from a resin composition. When the base film is a biaxially stretched film, the PAS resin (A) constituting the matrix crystallizes in a state in which its molecular chain is stretched, so that a film with high dimensional accuracy can be obtained. In one embodiment of such a film, the PAS resin (A) is used as a matrix (continuous phase), and particles (dispersed phase) containing a thermoplastic resin (B) other than the PAS resin are dispersed in this matrix. The modified elastomer (C) is present on the surface of the particles of the thermoplastic resin (B) (i.e., the interface between the matrix and the particles), inside the particles of the thermoplastic resin (B), or as particles (dispersed phase) separate from the particles of the thermoplastic resin (B).
[0081] The present inventors also believe that the modified elastomer (C) also functions as a compatibilizer between the PAS resin (A) and the thermoplastic resin (B), and thus the particles are finely dispersed in the matrix, suppressing film breakage during stretching, improving the mechanical strength (folding endurance, etc.) of the biaxially stretched film, and improving the mechanical strength of the laminate. Furthermore, the present inventors believe that the combined use of the modified elastomer (C) with a silane coupling agent further improves the adhesiveness at the interface between the matrix and the particles, and further improves the mechanical strength (folding endurance, etc.) of the biaxially stretched film and the laminate.
[0082] The base film is preferably a biaxially stretched film obtained by biaxially stretching an unstretched sheet obtained from a resin composition.
[0083] The biaxially stretched film may have at least one layer made of the base film composition of the present invention as the outermost layer, and may also be a biaxially stretched laminate film in which a layer made of another resin composition is laminated directly or via an adhesive layer or the like.
[0084] The method for producing the biaxially stretched laminate film used in the present invention is not particularly limited, but for example, in the case of a laminated structure, the resins or resin mixtures used for each resin layer are heated and melted in separate extruders, laminated in the molten state in the desired laminated structure by a coextrusion lamination die method, a feed block method, or the like, and then molded into a sheet by an inflation method, a T-die chill roll method, etc. This coextrusion method is preferable because it allows relatively free adjustment of the thickness ratio of each layer and can produce an unstretched laminated sheet with excellent cost performance.
[0085] In the method for producing the unstretched sheet, first, the resin composition is dried at 140°C for 3 hours or more, and then fed into an extruder heated to 280 to 320°C. The molten material is then extruded into a sheet from a T-die. Next, the sheet-like kneaded product is cooled and solidified by being brought into close contact with a cooling roll having a surface temperature of 20 to 50° C. In this way, an unstretched sheet in a non-oriented state is obtained.
[0086] Next, in the case of biaxial stretching, the unstretched sheet is biaxially stretched. The stretching method may be a sequential biaxial stretching method, a simultaneous biaxial stretching method, or a combination of these methods. When biaxially stretching is performed by the sequential biaxial stretching method, for example, the obtained unstretched sheet is heated with a group of heating rolls and stretched in the longitudinal direction (MD direction) by 1.5 to 4 times (preferably 2 to 3.8 times) in one stage or in two or more stages, and then cooled with a group of cooling rolls at 30 to 60°C. The stretching temperature is preferably from the glass transition temperature (Tg) of the PAS resin (A) to Tg+40°C, more preferably from Tg+3°C to Tg+30°C, and even more preferably from Tg+3°C to Tg+20°C.
[0087] Next, the film is stretched in the transverse direction (TD) by using a tenter. Both ends of the film stretched in the MD are held by clips and introduced into the tenter, where it is stretched in the TD. The stretching ratio is preferably from 1.5 to 4 times, and more preferably from 2 to 3.8 times. The stretching temperature is preferably from Tg to Tg+40°C, more preferably from Tg+3°C to Tg+30°C, and further preferably from Tg+3°C to Tg+20°C.
[0088] The ratio of the stretching ratio in the width direction (TD direction) of the biaxially stretched film to the stretching ratio in the width direction (MD direction) of the biaxially stretched film (longitudinal direction (TD direction)) / (width direction (MD direction)) is preferably 0.8 to 1.2, and more preferably 0.9 to 1.1.
[0089] The biaxially stretched film is then heat set while under tension or relaxed in the width direction. The heat setting temperature is not particularly limited, but is preferably 200 to 280°C, more preferably 220 to 280°C, and even more preferably 240 to 275°C. The heat setting may be carried out in two stages by changing the heat setting temperature. In this case, it is preferable that the heat setting temperature in the second stage is higher by +10 to 40°C than the heat setting temperature in the first stage. A biaxially stretched film heat set at a heat setting temperature in this range has improved heat resistance and mechanical strength. The heat setting time is preferably 1 to 60 seconds.
[0090] Furthermore, this biaxially stretched film is cooled while being relaxed in the width direction in a temperature zone of 50 to 280° C. The relaxation rate is preferably 0.5 to 10%, more preferably 2 to 8%, and further preferably 3 to 7%.
[0091] The film of the present invention may be further heat-treated to enhance its thermal stability. Examples of heat-treatment methods after stretching include known methods such as a method of blowing hot air, a method of irradiating infrared rays, and a method of irradiating microwaves. Among these, the method of blowing hot air is preferred because it can heat uniformly and precisely. The heat treatment temperature is preferably from 150 to 260°C, and more preferably from 160 to 240°C. The heat treatment time is preferably from 3 to 300 seconds, and more preferably from 5 to 100 seconds.
[0092] If necessary, the base film of the present invention may be subjected to a treatment for improving the adhesiveness of its surface. Examples of methods for improving the adhesiveness include corona treatment, plasma treatment, acid treatment, and flame treatment.
[0093] Although the base film and laminate of the present invention have been described above, the present invention is not limited to the configurations of the above-mentioned embodiments. For example, the film and laminate of the present invention may each have any other configuration added to the configuration of the above-mentioned embodiment, or may be substituted with any configuration that exhibits a similar function.
[0094] [Laminate] The laminate of the present invention has the above-mentioned base film (preferably a biaxially oriented film or a biaxially oriented laminate film), a first metal layer formed on the surface of the base film, and a second metal layer formed on the surface of the first metal layer.
[0095] The laminate according to the present invention may have a structure such as metal layer (conductive layer including at least a first metal layer and a second metal layer)-film, metal layer-film-metal layer, metal layer-film-metal layer-film, metal layer-metal layer-film, metal layer-metal layer-film, metal layer-metal layer-film-metal layer, etc. Also, the laminate may have a structure in which a plurality of the above laminates are laminated.
[0096] Because the base film of such a laminate has excellent dielectric properties, it can be processed into flexible printed circuit boards (FPC) and flexible flat cables (FFC) that are suitable for next-generation high-speed transmission. Furthermore, if a biaxially stretched film with excellent stretching uniformity is used, the laminate has excellent thickness uniformity and the variation in the dielectric constant can be suppressed. Furthermore, between the film and the metal layer, for example, an intermediate layer having a function of improving the adhesion between them may be provided.
[0097] [First metal layer] The first metal layer can be provided by forming a metal layer on the surface of a base film containing at least a polyarylene sulfide resin (A) and a thermoplastic resin (excluding polyarylene sulfide resin) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher. The first metal layer serves to improve adhesion between the base film and the second metal layer or the copper plating layer.
[0098] The first metal layer can be formed from Ni, Cu, Cr, or an alloy containing one or more of these metals, but using at least Ni or an alloy containing Ni and Cr is preferable in that it can improve adhesion between the base film and the second metal layer or copper plating layer. That is, the proportion of Ni present in the first metal layer is preferably in the range of 10 mass % to 97 mass %, and more preferably in the range of 30 mass % to 95 mass %. Also, When the first metal layer contains Cu, the proportion of Cu present in the first metal layer is preferably in the range of 5 mass % to 90 mass %, and more preferably in the range of 20 mass % to 70 mass %. Furthermore, when the first metal layer contains Cr, the proportion of Cr present in the first metal layer is preferably in the range of 3 mass % to 50 mass %, and more preferably in the range of 5 mass % to 40 mass %. Furthermore, when the first metal layer contains Ni and Cr, the Ni ratio is preferably in the range of 50 to 97 mass %, and the Cr ratio is preferably in the range of 3 to 50 mass %.
[0099] The thickness of the first metal layer is not particularly limited, but the thickness is preferably within the range of 1 to 500 nm, and more preferably within the range of 5 to 100 nm. The thickness of the first metal layer can be determined by XPS or TEM, but the thickness can also be estimated from the film formation rate of sputtering. When estimating the thickness from the film formation rate of sputtering, sputtering is performed to a thickness of 0.1 μm (100 nm) or more at an arbitrary film formation rate, and the thickness can be measured from the relationship between the sputtering time and the sputtered thickness.
[0100] The first metal layer may be formed on the surface of the base film, and may be formed on at least one side of the base film, or may be formed on both sides. When the first metal layer is provided on both sides of the base film, each side may be sputtered, or both sides may be sputtered at the same time.
[0101] [Step of forming the first metal layer] In the step of forming a first metal layer, a metal layer is formed by sputtering on the surface of a base film containing a polyarylene sulfide resin (A) and a thermoplastic resin (B) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher. The first metal layer can be formed from Ni or an alloy containing one or more of the metals Ni and Cu or Cr, and is preferably an alloy containing Ni and Cu or Ni and Cr.
[0102] The first metal layer may be formed on the surface of the base film, and may be formed on at least one side of the base film, or may be formed on both sides. When the first metal layer is provided on both sides of the base film, each side may be sputtered, or both sides may be sputtered at the same time.
[0103] The first metal layer can be formed by a known method, such as a direct current magnetron sputtering method, using a sheet-type sputtering device or a roll-to-roll type sputtering device.
[0104] [Second metal layer] The second metal layer can be provided by forming a metal layer on the surface of the first metal layer. The second metal layer functions as a conductive layer when a copper plating layer is subsequently provided. By providing the second metal layer, the variation in surface resistance value can be suppressed, and the variation in film thickness during the subsequent copper plating can be reduced.
[0105] The second metal layer is formed from an alloy containing Cu, and the proportion of Cu present in the second metal layer is preferably 90 mass % or more.
[0106] The thickness of the second metal layer is not particularly limited, but the thickness is preferably within the range of 1 to 50 μm, and more preferably within the range of 5 nm to 30 μm. The thickness of the second metal layer can be determined by XPS or TEM, but can also be estimated from the film formation rate of sputtering. When estimating the thickness from the film formation rate of sputtering, sputtering is performed to a thickness of 0.1 μm (100 nm) or more at an arbitrary film formation rate, and the thickness can be measured from the relationship between the sputtering time and the sputtered thickness.
[0107] The second metal layer may be formed on the surface of the first metal layer, and may be formed on at least one side of the first metal layer, or may be formed on both sides. When the second metal layer is provided on both sides of the base film, each side may be sputtered and plated, or both sides may be sputtered and plated at the same time.
[0108] [Step of forming second metal layer] In the step of forming the second metal layer, a metal layer is formed on the surface of the first metal layer. The second metal layer is preferably formed from an alloy containing 90 mass % or more of Cu.
[0109] The thickness of the second metal layer is not particularly limited, but the thickness is preferably within the range of 1 nm to 50 μm, and more preferably within the range of 5 nm to 30 μm. The thickness of the second metal layer can be estimated in the same manner as the thickness of the first metal layer.
[0110] When the base film has a first metal layer on both sides, the second metal layer may be provided by sputtering or plating each side at a time, or the second metal layer may be provided by sputtering or plating both sides at the same time.
[0111] The method for forming the second metal layer may be a known method, such as electroless plating, electrolytic plating, vapor deposition, DC magnetron sputtering, etc. When DC magnetron sputtering is used, the second metal layer may be formed by a sheet-type sputtering device or a roll-to-roll type sputtering device.
[0112] [Copper plating layer] The second metal layer constituting the laminate of the present invention may be a copper plating layer, or may have a structure in which a copper plating layer is further formed on the surface of the second metal layer. For example, when the laminate is used for a printed wiring board or the like, the second metal layer is provided for the purpose of forming a highly reliable wiring pattern that can maintain good electrical conductivity for a long period of time without causing disconnection or the like.
[0113] The copper plating layer according to the present invention is a layer formed on the surface of the first metal layer or the surface of the second metal layer, and the method of forming the copper plating layer is preferably a method of forming the copper plating layer by plating. Examples of the plating method include wet plating methods such as electrolytic plating and electroless plating, which can easily form the copper plating layer. Two or more of these plating methods may be combined. For example, the copper plating layer may be formed by performing electroless plating and then electrolytic plating.
[0114] The electroless plating method is a method in which, for example, an electroless plating solution is brought into contact with a metal constituting a first metal layer or a second metal layer, thereby precipitating a metal such as copper contained in the electroless plating solution and forming an electroless plating layer (film) consisting of a metal film.
[0115] The plating solution used for electroless plating may contain Cu, a reducing agent, and a solvent such as an aqueous medium or an organic solvent.
[0116] Examples of the reducing agent include dimethylaminoborane, hypophosphorous acid, sodium hypophosphite, dimethylamineborane, hydrazine, formaldehyde, sodium borohydride, and phenol.
[0117] The electroless plating solution may contain, as necessary, a complexing agent such as a monocarboxylic acid such as acetic acid or formic acid; a dicarboxylic acid compound such as malonic acid, succinic acid, adipic acid, maleic acid, or fumaric acid; a hydroxycarboxylic acid compound such as malic acid, lactic acid, glycolic acid, gluconic acid, or citric acid; an amino acid compound such as glycine, alanine, iminodiacetic acid, arginine, aspartic acid, or glutamic acid; an aminopolycarboxylic acid compound such as iminodiacetic acid, nitrilotriacetic acid, ethylenediaminediacetic acid, ethylenediaminetetraacetic acid, or diethylenetriaminepentaacetic acid; or a soluble salt (sodium salt, potassium salt, ammonium salt, or the like) of these organic acids, or an amine compound such as ethylenediamine, diethylenetriamine, or triethylenetetramine.
[0118] The electrolytic plating method is a method in which, for example, an electric current is passed through an electrolytic plating solution in contact with the surface of a metal constituting a first metal layer or a second metal layer, causing metal ions such as copper contained in the electrolytic plating solution to precipitate on the surface of the first metal layer or the second metal layer placed at the cathode, thereby forming an electrolytic plating layer (metal coating).
[0119] The plating solution used for electrolytic plating may, for example, contain copper sulfide, sulfuric acid, and an aqueous medium. Specifically, the plating solution may contain copper sulfate, sulfuric acid, and an aqueous medium.
[0120] The electroless plating solution and the electrolytic plating solution are preferably used at a temperature in the range of 20 to 98°C.
[0121] The thickness of the copper plating layer according to the present invention can be any value as required, but is preferably in the range of 1 μm to 50 μm, more preferably 5 μm to 30 μm. The thickness of the copper plating layer according to the present invention can be adjusted by controlling the treatment time, current density, amount of plating additives used, etc. in the plating process when forming the copper plating layer. EXAMPLES
[0122] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these.
[0123] [Example 1] <Base film manufacturing> A mixture was obtained by uniformly mixing 84.5 mass% of polyphenylene sulfide resin (PPS resin) (A) (manufactured by DIC Corporation, linear type, melting point 280°C, melt viscosity (V6) at 300°C 110 Pa s) as polyarylene sulfide resin, 15 mass% of polyphenylene ether resin (manufactured by Mitsubishi Engineering Plastics, poly(2,6-dimethyl-1,4-phenylene ether), glass transition temperature 210°C) as thermoplastic resin (B) and 0.5 mass% of 3-glycidoxypropyltriethoxysilane as a silane coupling agent in a tumbler.
[0124] The polyphenylene sulfide resin has a carboxyl group at its molecular terminal. Hereinafter, polyphenylene sulfide resin will be referred to as "PPS" and 3-glycidoxypropyltriethoxysilane will be referred to as "silane coupling agent."
[0125] Next, the mixture obtained above was put into a vented twin screw extruder (manufactured by Japan Steel Works, Ltd., "TEX-30α"), and then melt extruded and discharged in the form of strands under the conditions of a discharge rate of 20 kg / hr, a screw rotation speed of 300 rpm, a cylinder set temperature on the raw material supply port side of 200°C, other cylinder set temperatures of 280 to 320°C, and a resin temperature in the strand die of about 300°C. The mixture was then cooled with water at a temperature of 30°C and cut to produce a resin composition.
[0126] Next, this resin composition was dried at 140° C. for 3 hours, and then charged into a full-flight screw single-screw extruder and melted under conditions of 280 to 310° C. The molten resin composition was extruded from a T-die and then cooled in close contact with a chill roll set at 40° C. to produce an unstretched sheet. Next, the unstretched sheet was biaxially stretched 3.0x3.0 times at 100°C using a batch-type biaxial stretching machine (Imoto Manufacturing Co., Ltd.) to obtain a base film with a thickness of 50 μm. The obtained film was then fixed to a mold and heat-set in an oven at 275°C to produce a biaxially stretched film as the base film.
[0127] Furthermore, the obtained biaxially stretched film was left to stand in a heating furnace (corresponding to an annealing furnace) at 180° C. for 60 seconds and then cooled to room temperature to obtain an annealed base film.
[0128] The average particle size of the particles in the produced base film was measured as follows. Specifically, the produced biaxially stretched film was cut by ultra-thin sectioning in (a) a direction parallel to the longitudinal direction and perpendicular to the film surface, and (b) a direction parallel to the width direction and perpendicular to the film surface. Scanning electron microscope (SEM) photographs of the cut surfaces (a) and (b) of the cut film were taken at 2000 times magnification, and the obtained images were enlarged to A3 size. Fifty dispersed phases were randomly selected from the enlarged SEM photographs, and the maximum diameter of the dispersed phase on each of the fracture surfaces (a) and (b) was measured, and the average diameter was calculated by combining the two directions of the cut surfaces (a) and (b). As a result, the average particle size of the particles in the biaxially stretched film was 1.0 μm.
[0129] In addition, the cut biaxially stretched film was subjected to SEM-EDS analysis to analyze the components that make up the matrix and particles of the base film. As a result, it was found that the component that makes up the matrix is PPS, and the component that makes up the particles is PPE resin.
[0130] <Manufacture of the first metal layer> The obtained base film was cut to a width of 200 mm and a length of 200 mm, and set in a magnetron sputtering device. An alloy target of Ni and Cr was used for the sputtering cathode. The target used had an alloy with a Cr ratio (atomic percentage) of 25 Atom% (22.8 mass%). A first metal layer made of an alloy of Ni and Cr was formed on the surface of the base film. Here, the thickness of the first metal layer was adjusted to be 30 nm.
[0131] <Manufacture of the second metal layer> A second metal layer was formed on the surface of the first metal layer. The base film on which the first metal thin film layer was formed was set in a magnetron sputtering device. A Cu target was used as the sputtering cathode. A second metal layer made of Cu was formed on the surface of the base film. Here, the thickness of the second metal layer was adjusted to be 80 nm.
[0132] <Preparation of copper plating layer> Each sample was left in a room for 24 hours and then electrolytic plating was performed. As a pretreatment for electrolytic plating, an acid treatment was performed using a 10% by mass aqueous sulfuric acid solution at a temperature of 30°C to remove copper oxide present on the surface of the second metal layer. A copper plating film having a thickness of 12.0 μm was formed on the surface of the second metal layer by electrolytic plating, to obtain a copper-clad laminate. Here, a solution containing copper sulfate, sulfuric acid, hydrochloric acid, and additives was used as the copper plating solution.
[0133] [Example 2] A base film and a copper-clad laminate were produced in the same manner as in Example 1, except that the thickness of the second metal layer was adjusted to 12 μm and no copper plating film was formed.
[0134] [Example 3] A base film and a copper-clad laminate were produced in the same manner as in Example 1, except that 94.5% by mass of PPS resin (A) and 5% by mass of polycarbonate resin (manufactured by Mitsubishi Engineering Plastics Chemical Co., Ltd., glass transition temperature 145°C, hereinafter sometimes referred to as "PC") and 0.5% by mass of silane coupling agent were used as the thermoplastic resin (B). The average particle size of the particles in the biaxially stretched film was measured in the same manner as in Example 1 and was found to be 1.3 μm. Furthermore, the components of the base film were analyzed in the same manner as in Example 1, and it was found that PC resin particles were dispersed in the PPS matrix.
[0135] [Example 4] A base film and a copper-clad laminate were produced in the same manner as in Example 1, except that 89.5 mass% of PPS resin (A), 10 mass% of polyethersulfone resin (manufactured by BASF Ltd., glass transition temperature 225°C, hereinafter sometimes referred to as "PES") as thermoplastic resin (B), and 0.5 mass% of silane coupling agent were used. Furthermore, the average particle size of the particles in the biaxially stretched film was measured in the same manner as in Example 1, and was found to be 1.2 μm. Furthermore, the components of the base film were analyzed in the same manner as in Example 1, and it was found that PES resin particles were dispersed in the PPS matrix.
[0136] [Example 5] A base film and a copper-clad laminate were produced in the same manner as in Example 1 using 84.5 mass% of PPS resin (A), 15 mass% of polyphenylene sulfone resin (manufactured by BASF Ltd., glass transition temperature 220°C, hereinafter sometimes referred to as "PPSU") as thermoplastic resin (B), and 0.5 mass% of a silane coupling agent. The average particle size of the particles in the biaxially stretched film was measured in the same manner as in Example 1 and was found to be 1.1 μm. Furthermore, the components of the base film were analyzed in the same manner as in Example 1, and as a result, it was found that PPSU resin particles were dispersed in the PPS matrix.
[0137] [Example 6] A base film and a copper-clad laminate were produced in the same manner as in Example 1, except that 94.5 mass% of PPS resin (A), 5 mass% of polyetherimide resin (manufactured by SABIC Corporation, glass transition temperature 216°C, hereinafter sometimes referred to as "PEI"), and 0.5 mass% of a silane coupling agent were used. The average particle size of the particles in the biaxially stretched film was measured in the same manner as in Example 1, and was found to be 1.4 μm. Furthermore, the components of the base film were analyzed in the same manner as in Example 1, and it was found that PES resin particles were dispersed in the PPS matrix.
[0138] [Example 7] A base film was produced in the same manner as in Example 1, except that 84.5% by mass of PPS resin (A), 15% by mass of polysulfone resin (manufactured by SOLVAY Corporation, glass transition temperature 190°C, hereinafter sometimes referred to as "PSU") as thermoplastic resin (B), and 0.5% by mass of silane coupling agent were used. The average particle size of the particles in the biaxially stretched film was measured in the same manner as in Example 1 and was found to be 1.3 μm. Furthermore, the components of the base film were analyzed in the same manner as in Example 1, and as a result, it was found that particles of PSU resin were dispersed in the PPS matrix.
[0139] [Example 8] A base film was produced in the same manner as in Example 1, except that 84.5% by mass of PPS resin (A), 15% by mass of EA-2000 (PFA type, manufactured by AGC Inc., melting point 300°C, glass transition temperature 94°C, hereinafter sometimes referred to as "modified PFA"), which is a fluorine-containing resin having functional groups in the thermoplastic resin (B), and 0.5% by mass of a silane coupling agent were used. The average particle size of the particles in the biaxially stretched film was measured in the same manner as in Example 1 and was found to be 1.3 μm. Furthermore, the components of the base film were analyzed in the same manner as in Example 1, and as a result, it was found that a fluorine-containing resin was dispersed in the PPS matrix.
[0140] [Example 9] A base film and a copper-clad laminate were produced in the same manner as in Example 1, except that 74.5% by mass of PPS resin (A), 10% by mass of PPE resin as thermoplastic resin (B), 15% by mass of EA-2000 as fluorine-containing resin, and 0.5% by mass of silane coupling agent were used.
[0141] [Example 10] A base film and a copper-clad laminate were produced in the same manner as in Example 1, except that 85 mass % of the PPS resin (A) and 15 mass % of the PPE resin were used as the thermoplastic resin (B).
[0142] [Example 11] A base film and a copper-clad laminate were produced in the same manner as in Example 1, except that 82.5% by mass of PPS resin (A), 15% by mass of modified PFA resin as thermoplastic resin (B), 2% by mass of Bondfast 7L (manufactured by Sumitomo Chemical Co., Ltd., ethylene / glycidyl methacrylate / methyl acrylate=70 / 3 / 27 (mass%), hereinafter sometimes referred to as "BF7L") as the modified elastomer (C) having reactive groups, and 0.5% by mass of a silane coupling agent were used.
[0143] [Example 12] Except for using an alloy target of Ni and Cu for the sputtering cathode of the first metal layer, a base film and a copper-clad laminate were produced in the same manner as in Example 8. The target used was an alloy with a Cu ratio (atomic percentage) of 60 Atom% (61.9 mass%).
[0144] [Example 13] Except for using an alloy target of Cu and Ti for the sputtering cathode of the second metal layer, a base film and a copper-clad laminate were produced in the same manner as in Example 1. The target used was an alloy with a Ti ratio (atomic percentage) of 5 Atom% (3.8 mass%). [Comparative Example 1] A base film and a copper-clad laminate were produced in the same manner as in Example 1, except that only the PPS resin (A) was charged into a vented twin-screw extruder (manufactured by The Japan Steel Works, Ltd., "TEX-30α").
[0145] [Comparative Example 2] A mixture was obtained by uniformly mixing 84.5% by mass of PPS resin (A), 15% by mass of PPE resin in thermoplastic resin (B), and 0.5% by mass of silane coupling agent in a tumbler. The mixture was then fed into a vented twin-screw extruder (manufactured by Japan Steel Works, Ltd., "TEX-30α"). The mixture was then melt-extruded and extruded in a strand shape under the conditions of a discharge rate of 20 kg / hr, a screw rotation speed of 300 rpm, a cylinder set temperature on the raw material supply port side of 200°C, a cylinder set temperature of 280 to 320°C on the other side, and a resin temperature of about 300°C in the strand die, and then cooled with water at a temperature of 30°C, followed by cutting to produce a resin composition.
[0146] Next, this resin composition was dried at 140°C for 3 hours, and then put into a single-screw extruder with a full-flight screw and melted under the condition of 280 to 310°C. The molten resin composition was extruded from a T-die, and then cooled in close contact with a chill roll set at 40°C to produce an unstretched film with a thickness of 50 μm. The unstretched film obtained was fixed to a mold and heat-set in an oven at 275°C to produce a biaxially stretched film as a base film. Furthermore, a first metal layer, a second metal layer, and a copper plating layer were produced on the unstretched film in the same manner as in Example 1, and a copper-clad laminate was produced.
[0147] [Comparative Example 3] A base film and a copper-clad laminate were produced in the same manner as in Example 1, except that 84.5% by mass of PPS resin was used, 15% by mass of general-purpose polystyrene resin (manufactured by DIC Corporation, glass transition temperature 100°C, hereinafter sometimes referred to as "GPPS") was used as the thermoplastic resin (B), and 0.5% by mass of a silane coupling agent was used.
[0148] [evaluation] 1.Stretchability The success rate of biaxially stretching 30 unstretched sheets to obtain a stretched film without breaking. ◎: 95% or more 〇: 80% or more ×: Less than 80%
[0149] 2. Dielectric properties of the base film The dielectric constant and dielectric loss tangent were measured based on the cavity resonance method specified in JIS C 2565:1992. Specifically, a strip of 3 mm width × 150 mm length was prepared from the base film. The prepared strip was then left to stand for 24 hours in an environment of 23°C and 50% RH, and the dielectric constant and dielectric loss tangent at a frequency of 5 GHz were measured by the cavity resonance method using ADMS010c series (manufactured by AET Corporation).
[0150] 3. Initial adhesion A sample measuring 10 mm wide x 70 mm long was cut from the copper-clad laminate after electrolytic plating, and tested according to the test method specified in JIS K 6854: 1999. The adhesion strength between the copper foil and the base film produced by electrolytic plating was measured and evaluated according to the following criteria. ◎;6N / cm or more ○: 5N / cm or more and less than 6N / cm ×: Less than 5N / cm
[0151] 4. Adhesion after heat resistance test After electrolytic plating, the copper-clad laminate was heated at 260°C for 5 minutes, then left at 24°C for 24 hours, after which a sample 10 mm wide x 70 mm long was cut out and tested according to the test method specified in JIS K 6854: 1999. The adhesion strength between the copper foil and base film produced by electrolytic plating was measured and evaluated according to the following criteria. ◎;5N / cm or more ○: 3N / cm or more and less than 5N / cm ×: Less than 3N / cm
[0152] 5.Dimensional accuracy A 200 x 250 mm sample was cut out from the copper-clad laminate, holes were drilled at 50 mm intervals, and the distance between each hole was measured using the top left hole as the reference point. The sample was then etched and heated to 150°C for 30 minutes, after which the distance between each hole was measured again and the dimensional change was evaluated according to the following criteria. ◎: Less than 0.1% 〇;0.3% or less 0.1% or more ×: 0.3% or more
[0153] The results are shown in Tables 1 to 3.
[0154] [Table 1] *PAR: Polyarylene sulfide resin PPS; Polyphenylene sulfide resin PPE; Polyphenylene ether resin PC; polycarbonate resin PES; Polyethersulfone resin PPSU; Polyphenylene sulfone resin PEI; Polyetherimide resin PSU; Polysulfone resin Modified PFA; Modified perfluoroalkoxyalkane Ni; Nickel Cr; Chromium Cu; Copper Ti; Titanium
[0155] [Table 2]
[0156] [Table 3]
[0157] [Table 4] *GPPS; General-purpose polystyrene resin
Claims
1. A base film containing a polyarylene sulfide-based resin (A) and a thermoplastic resin (excluding polyarylene sulfide-based resins) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher; a first metal layer made of an alloy containing Ni and formed on a surface of the base film; a second metal layer formed on a surface of the first metal layer; A laminate comprising:
2. 2. The laminate according to claim 1, wherein the base film is a biaxially oriented film.
3. 3. The laminate according to claim 1, wherein the base film has a dielectric constant of 3.3 or less.
4. 3. The laminate according to claim 1, wherein the blending ratio of the polyarylene sulfide-based resin (A) is 51 to 97% by mass with respect to 100% by mass of the total amount of the base film.
5. 3. The laminate according to claim 1 or 2, wherein the thermoplastic resin (excluding polyarylene sulfide-based resin) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher contains at least one polymer selected from the group consisting of polyphenylene ether-based resins, polycarbonate resins, polyethersulfone resins, polyphenylsulfone resins, polyetherimide resins, polysulfone resins, and fluorine-containing resins.
6. The laminate according to claim 1 or 2, wherein the blending ratio of the thermoplastic resin (excluding polyarylene sulfide resin) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher is 3 to 49 mass% relative to 100 mass% of the total amount of the base film.
7. The first metal layer made of an alloy containing Ni is an alloy containing Ni and Cr, The laminate according to claim 1 or 2, wherein the metal species constituting the second metal layer is a metal containing 90 mass % or more of Cu.
8. The laminate according to claim 1 or 2, wherein the first metal layer made of an alloy containing Ni is an alloy containing Ni and Cr, and the proportion of Cr present in the alloy is 3 to 50 mass%.
9. 3. The laminate according to claim 1, further comprising a modified elastomer (C) having reactive groups in the base film.
10. 10. The laminate according to claim 9, wherein the modified elastomer (C) comprises an olefin polymer having at least one functional group selected from the group consisting of an epoxy group and an acid anhydride group.
11. The laminate according to claim 9, wherein the blending ratio of the modified elastomer (C) is in the range of 1 to 15 mass% relative to 100 mass% of the total amount of the base film.
12. The laminate according to claim 10, wherein the blending ratio of the modified elastomer (C) is in the range of 1 to 15 mass% relative to 100 mass% of the total amount of the base film.
13. The laminate according to claim 1 or 2, further comprising 0.01 to 5 mass % of a silane coupling agent (D) containing at least one functional group selected from an epoxy group, an amino group, and an isocyanate group in the base film.
14. 3. The laminate according to claim 1, wherein the thermoplastic resin (B) (excluding polyarylene sulfide resin) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher has an average dispersion diameter of 5 μm or less.
15. An electronic device using the laminate according to claim 1 or 2.
Citation Information
Patent Citations
Two-layer flexible board and manufacturing method thereof
JP2006013152A
Laminate
JP2007276456A